LB-8. Summary of COVID-Related Impact on Cabotegravir and Rilpivirine Long-Acting (CAB+RPV LA) Dosing Across the Six Ongoing Global Phase IIb and IIIb Clinical Trials. (31st December 2020) - D'Amico, Ronald; Benn, Paul; McCoig, Cynthia C; McCoig, Cynthia C; Griffith, Sandy; Hudson, Krischan J; Sutton, Kenneth; Sutton, Kenneth; Harrington, Conn M; Wu, Sterling; Williams, Will; Hove, Kai S; et al.
Abstract: Background: SARS-CoV-2 (COVID-19) has disrupted healthcare service delivery globally. CAB+RPV LA is a novel, long-acting antiretroviral therapy (ART) currently in development and is administered intramuscularly monthly or every 2 months by a healthcare provider. COVID-19 and the resultant restrictions on access to some clinical trial sites presents challenges to the continuous delivery ('implementation fidelity') of CAB+RPV LA during a pandemic. Methods: Descriptive analyses were conducted using aggregated data from ongoing CAB+RPV LA clinical trials (LATTE-2, ATLAS, ATLAS-2M, FLAIR, POLAR, and CUSTOMIZE) to evaluate impact of COVID-19 on LA dosing. Data through 15 July 2020 were aggregated, categorized, and summarized to show trends. Data collection is continuously ongoing. Results: As of 15 July 2020, 1831 participants are currently on CAB+RPV LA across these clinical studies. As of 15 July, 113 (6%) participants had injection visits that were impacted by COVID-19. LA dosing was interrupted in 51 (45%) participants due to clinic closure or staffing constraints, 9 (8%) for self-quarantine, 11 (10%) for confirmed or suspected COVID-19, and 42 (37%) for other reasons. Among participants impacted, 64 (58%) were from N. America, 29 (26%) Europe, 14 (13%) S. Africa, and 3 (3%) Latin America. Majority of participants were male (87, 79%), white (74, 65%), with median age 35 years. Mitigation strategies included short-term oral therapy with CAB+RPV (78, 69%), short-term standard of care ART (28, 25%), and rescheduling of LA injections (6, 5%). Although some are still receiving oral therapy, current median duration of oral therapy has been 45 days. To date, 65 (58%) have restarted LA and viral load data collection is ongoing. No suspected or confirmed virologic failure was observed for any participant impacted by COVID-19 to date. Conclusion: In the midst of the global pandemic, no treatment interruptions were seen across the ongoing CAB+RPV LA clinical studies. Missed visits were manageable and successfully mitigated, primarily by temporary transition to oral therapy with no resultant virologic failure or emerging resistance through 15 July 2020. CAB+RPV LA is a new HIV-1 treatment modality that has demonstrated implementation fidelity across clinical studies during the current COVID-19 pandemic. Disclosures: Ronald D'Amico, DO, MSc, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Paul Benn, MB ChB FRCP, ViiV Healthcare (Employee, Shareholder) Cynthia C. McCoig, MD, ViiV Healthcare (Employee) Cynthia C. McCoig, MD, ViiV Healthcare (Individual(s) Involved: Self): Employee Sandy Griffith, PharmD, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Krischan J. Hudson, PhD, MPH, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Kenneth Sutton, MA, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Kenneth Sutton, MA, GlaxoSmithKline (Individual(s) Involved: Self): Shareholder; ViiV Healthcare (Individual(s) Involved: Self): Employee Conn M. Harrington, BA, ViiV Healthcare (Employee) Sterling Wu, PhD, GlaxoSmithKline (Employee, Shareholder) Kai S. Hove, MRes, GSK (Independent Contractor) E Jane Fricker, BSc. (Hons) Applied Biochemistry, GSK (Employee, Shareholder) Parul Patel, PharmD, ViiV Healthcare (Employee) David Margolis, MD, MPH, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) David Margolis, MD, MPH, GlaxoSmithKline (Individual(s) Involved: Self): Shareholder; ViiV Healthcare (Individual(s) Involved: Self): Employee